Effect of Watermelon Albedo Substitution on the Quality of Watermelon Syrup - Faiza, Urizinta Jarianti; Anggraini, Ezi; Faridah, Anni; Mustika, Sari (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
Watermelon, a fruit from the Cucurbitaceae family, is known for its sweet and juicy pulp, rich in nutrients like vitamin C, vitamin A, and lycopene. A study aims to assess the impact of using watermelon albedo, the white part of the rind often discarded, in making watermelon syrup, using a specified recipe. The research analyzes various aspects like sugar content, pH, viscosity, and sensory properties such as taste, aroma, texture, and color. The study is an experimental one following the Complete Randomized Design (CRD) method, with primary data collected from 20 panelists evaluating the watermelon syrup quality with albedo substitution, applying 4 treatments and 3 repetitions. This aims to explore the potential of utilizing watermelon albedo, usually considered waste, for its fiber and nutrient content in food applications.The data obtained then tabulated in the form of tables and performed Analysis of Variance (ANOVA), if Fh>Ft then continued with the Duncan Test. In this study, watermelon albedo was used as a substitute material in the manufacture of watermelon syrup with a variation in the percentage of substitution of 0%, 15%, 30%, and 45% which significantly affected the quality of thick texture 4.60 (450gr albedo), homogeneous texture quality 5.03 (150gr albedo), and taste 3.50 (550 gr albedo). The results of the quality of watermelon syrup with the influence of the best watermelon albedo substitution are in the second treatment (X1) with the addition of albedo as much as 150gr both from the color, aroma, texture and taste sensory tests.